Cloud technologies in secondary schools - S. V. Shokaliuk; I. S. Zakarlyuka (Academy of Cognitive and Natural Sciences, 2015)
The purpose of this study is to determine the role and place of cloud technologies in the modern school, the main task - determining components of cloud technology tools support individual learning school subjects, the object of study - the tools of support and e-learning in secondary schools, the subject - means cloud technologies for e-learning students, the main research method - a theoretical study. The system of cloud technology training tools for specific school subject consists of general education tools cloud technologies (tools for online e-learning materials development and online storage, cloud technology learning management tools) and specialized cloud technologies tools - browser-based system of programming and simulation (to support learning computer science), mathematical mobile environments (to support the study of mathematics), virtual online labs and simulation system (to support the study of physics, chemistry or biology) etc. The use of cloud technologies in the educational process of general education schools especially will solve the problem of providing equal access for students and teachers to high-quality educational resources in the classroom and in their spare time.